(untitled) - Mencken, Henry Louis (New York, 1960)
Sixty-nine political pieces drawn from Mencken's famous Monday columns in the Baltimore Evening Sun during the Twenties and Thirties
Keywords: United States,Presidents,Tổng thống,Hoa Kỳ; Politics and government,Election,Bầu cử,Chính phủ và chính trị; 1919-1933,1936,1936,1919-1933; United States,Hoa Kỳ